An Analysis of ‘PULSE 2’ Cultural Content and How Malaysian ESL Teachers Perceive IT (International Journal of Academic Research in Progressive Education and Development, 2022)
Imported English textbooks were introduced to Malaysian schools in line with Malaysia's new CEFR-aligned English language curriculum. One of the books is PULSE 2, in which concern about its foreign cultural content has been widely discussed. Therefore, this study aims to analyze the cultural categories displayed in the PULSE 2 textbook for Form 1 syllabus, investigate how foreign cultures and topics are introduced to the students, and identify the perception of Form 1 teachers of the textbook, specifically on its foreign cultural contents. This study employed mixed-method research. The first phase of the data collection involved quantitative analysis using a questionnaire administered to 30 Form 1 ESL teachers. The qualitative data were collected through content analysis and semi-structured interviews with Form 1 teachers from schools in Perak, Malaysia. The PULSE 2 textbook is culturally rich, especially with UK-centric contents. There is also an imbalance portrayal of cultural categories, and no reference is made to the Malaysian context in the book. Designing personal materials, comparing target and local cultures, and using resources such as visuals and web-based learning are the most common pedagogical methods used by Form 1 teachers in using this textbook with their students. Although the teachers positively perceived the textbook, they disclosed a mixed perception of its foreign cultural content. Despite this, PULSE 2 can still be exploited to benefit students.
Keywords: CEFR, Culture, PULSE 2, Textbook Analysis, Teachers’ Perception